Bringing Justice to Cambodia: Reflections on Dame Silvia Cartwright’s Role at the Khmer Rouge Tribunal - Kedgley Laidlaw, Anais (Victoria University of Wellington Law Review, 2014)
Dame Silvia Cartwright is one of New Zealand’s most distinguished woman jurists. While much is known about her celebrated New Zealand-based career, this article focuses on her more recent, and arguably more important role – as a judge at the Khmer Rouge Tribunal in Cambodia, tasked with bringing to justice those most responsible for the atrocities committed by the Khmer Rouge in the 1970s. This article is a portrait of Dame Silvia, underlining her role as a leading jurist and an inspiration to women, based on the personal experiences of the author. It is not intended to critically address any issue relating to the Tribunal.